Comparative Study of the Effects of Machine Parameters on DFIG and PMSG Variable Speed Wind Turbines During Grid Fault - Okedu, Kenneth E.; Al Tobi, Maamar; Al Araimi, Saleh (Frontiers in Energy Research, 2021)
This paper investigates the transient performance of the two Variable Speed Wind Turbines (VSWTs) that are widely employed in wind energy conversion, considering their machine parameters. The two wind turbines are the Doubly Fed Induction Generator (DFIG) and the Permanent Magnet Synchronous Generator (PMSG). The machine parameters of both wind turbines were varied considering different scenarios, while keeping other parameters constant, in order to study the behavior of the wind generators. The study was carried out using the same operation conditions for both wind turbines technology. The wind turbines were subjected to a severe three-phase to ground bolted fault, in order to test the robustness of their controllers during grid fault conditions. Efforts were made to carry out an extensive comparative study to investigate the machine parameters that have more influence on the stability of the different wind turbines considered in this study. Simulations were carried out in Power System Computer Aided Design and Electromagnetic Transient Including DC (PSCAD/EMTDC). Effective machine parameter selection could help solve Fault Ride Through (FRT) problems in a cost effective way for both VSWTs, without considering external circuitry and changing of the original architecture of the wind turbines.